Pole-Phase Modulation of Symmetrical 6-Phase Induction Motor Drive for Electric Vehicle With 1:2 Speed Control - S. V. Umredkar; R. Keshri; V. B. Borghate; M. M. Renge (IEEE Access)
The symmetrical 6-terminal pole-phase modulation (S6TPPM) induction motor drive (IMDrive) has proven to be a viable alternative to other drives in electric vehicles (EVs). The advantages of IMDrive combined with pole-phase modulation (PPM) provide the flexibility to expand the torque-speed range, enabling such drives to work efficiently under different driving conditions for EVs. An earlier study proposed a new winding pattern with three slots per pole per phase (3SPP) coupled with a preconfigured excitation pattern to help achieve high-pole and low-pole operations. However, there is a need to better control the pole-phase switching and acceleration of the drive. This study focuses on acceleration control over the 4-pole/1500 rpm and 2-pole/ 3000 rpm modes to achieve fast acceleration with high-torque and high-speed with low-torque required for the initial start and cruising respectively. Mathematical modeling based on the space vector theory to control S6TPPM IMDrive is presented. The dsPIC (digital signal controller) microcontroller-based voltage to frequency (V/f) control technique was employed to obtain manual control over the speed and torque of the drive and to keep the experimental setup simple as precision control is beyond the scope of the current study. The observations and results from the experiment show control of the speed of the IMDrive from 300 rpm to 3000 rpm and vice-versa.